2008
DOI: 10.4315/0362-028x-71.7.1460
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Prevalence in Seafood Imported into Japan

Abstract: A total of 353 samples of 29 types of seafood were tested for Salmonella prevalence and total microbial population. Salmonella enterica serotype Weltevreden was isolated from 2 of 47 black tiger prawn samples. The contamination levels of Salmonella were in a range of <30 to 40 most probable number per 100 g. In addition, one sample of black tiger prawns and two samples of white shrimp were positive for Salmonella invA gene on PCR assay. Although the mean aerobic bacterial count was greater than 4 log CFU/g in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
0
16
2
1
Order By: Relevance
“…Asai et al [62] reported that the examination of 353 samples of 29 types of seafood revealed that S. enterica serotype Weltevreden was isolated from two of 47 black tiger prawn samples. The contamination levels of Salmonella were in a range of <30-40 most probable number per 100 g. Asai concluded that these results indicate the possibility that shrimp and prawns contribute to food-borne infections.…”
Section: Reducing Salmonella Spp In Fish and Shellfishmentioning
confidence: 99%
“…Asai et al [62] reported that the examination of 353 samples of 29 types of seafood revealed that S. enterica serotype Weltevreden was isolated from two of 47 black tiger prawn samples. The contamination levels of Salmonella were in a range of <30-40 most probable number per 100 g. Asai concluded that these results indicate the possibility that shrimp and prawns contribute to food-borne infections.…”
Section: Reducing Salmonella Spp In Fish and Shellfishmentioning
confidence: 99%
“…Salmonella including serovar Weltevreden can form biofilms on food contact surfaces and resist sanitizer treatment in biofilms (Joseph et al 2001). In a study on 353 imported seafood items in Japan, 2/47 black tiger shrimp were positive, both with S. Weltevreden, and contamination levels in seafoods were < 30-40 MPN/100 g (Asai et al 2008). Analysis of 11,312 imported and 768 domestic seafood products in the US during 1990-1998 revealed that 10 % of imported and 2.8 % of domestic raw seafood were positive for Salmonella and the overall incidence was 7.2 % for imported and 1.3 % for domestic seafood (Heinitz et al 2000).…”
Section: Salmonellamentioning
confidence: 99%
“…One study of imported seafood (353 samples of 29 types of seafood) in Japan found two samples of black tiger shrimp at levels of < 30-40/100 g estimated by Most Probable Number (MPN) (Asai et al 2008). Considering that > 10 5 bacteria are required to cause infection (FAO/WHO 2002), it can be suggested that multiplication in fish would be necessary before the food is consumed (Table 5.1).…”
Section: Salmonellamentioning
confidence: 99%
“…A study of imported fish in Japan showed approximately 30-40 Salmonella cells/100g (Asai et al, 2008) and multiplication will therefore increase the risk of infection. Salmonella is a mesophilic organism and the growth rate of this organism is markedly reduced at temperatures above 15˚C while the growth of most strains is prevented at temperatures above 7˚C (ICMSF, 1996).…”
Section: Salmonellamentioning
confidence: 99%